2020
DOI: 10.1007/s42413-019-00054-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Community Well-being: A Proposal for an Emerging Area of Research

Abstract: We are calling for a new area of research on the nexus of community well-being and artificial intelligence (AI). Three components of this research we propose are (1) the development and use of well-being metrics to measure the impacts of AI; (2) the use of community-based approaches in the development of AI; and (3) development of AI interventions to safeguard or improve community well-being. After providing definitions of community, well-being, and community well-being, we suggest a definition of AI for use b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
(35 reference statements)
0
25
0
1
Order By: Relevance
“…In a workshop focusing explicitly on "AI for social good", the term "social good" is described as follows: "[social good] is intended to focus AI research on areas of endeavor that are to benefit a broad population in a way that may not have direct economic impact or return, but which will enhance the quality of life of a population of individuals through education, safety, health, living environment, and so forth" [36]. However, what exactly constitutes "AI for social good" [100,101] and what "makes AI socially good" [31] (p. 1) is still debated. Cowl et al argued that the following seven factors are essential for AI for social good: "(1) falsifiability and incremental deployment; (2) safeguards against the manipulation of predictors; (3) receiver-contextualised intervention; (4) receiver-contextualised explanation and transparent purposes; (5) privacy protection and data subject consent; (6) situational fairness; and (7) human-friendly semanticisation" [31] (p. 3).…”
Section: The Issue Of Social Goodmentioning
confidence: 99%
“…In a workshop focusing explicitly on "AI for social good", the term "social good" is described as follows: "[social good] is intended to focus AI research on areas of endeavor that are to benefit a broad population in a way that may not have direct economic impact or return, but which will enhance the quality of life of a population of individuals through education, safety, health, living environment, and so forth" [36]. However, what exactly constitutes "AI for social good" [100,101] and what "makes AI socially good" [31] (p. 1) is still debated. Cowl et al argued that the following seven factors are essential for AI for social good: "(1) falsifiability and incremental deployment; (2) safeguards against the manipulation of predictors; (3) receiver-contextualised intervention; (4) receiver-contextualised explanation and transparent purposes; (5) privacy protection and data subject consent; (6) situational fairness; and (7) human-friendly semanticisation" [31] (p. 3).…”
Section: The Issue Of Social Goodmentioning
confidence: 99%
“…The role of ethics in community development, community psychology, and community well-being has recently received attention in research and practice discourses (e.g., Bradley et al 2018;Kesten et al 2017;Musikanski et al 2020); however, more attention could be paid to how ethics link to well-being intentions, processes, and outcomes. Ethics and ethical frames help us define concepts and understand how concepts are operationalized by their processes and impacts (e.g., Dart et al 2010).…”
Section: The Ethics Of International Aidmentioning
confidence: 99%
“…Community well-being has been defined by several researchers as a set of multidimensional values including environmental, cultural, health, psychological well-being, subjective well-being, work, economic, and education (Bagnell et al 2017;Phillips and Wong 2017;Musikanski et al 2020;Hollander et al 2016). Musikanski et al (2020) assert that individual well-being can influence community well-being.…”
Section: Social Media and Community Well-beingmentioning
confidence: 99%
“…Community well-being has been defined by several researchers as a set of multidimensional values including environmental, cultural, health, psychological well-being, subjective well-being, work, economic, and education (Bagnell et al 2017;Phillips and Wong 2017;Musikanski et al 2020;Hollander et al 2016). Musikanski et al (2020) assert that individual well-being can influence community well-being. Several studies have found that individual well-being on social media could be directly impacted by a user's use of subjective well-being language (Yetim et al 2014;Gerson et al 2016; Tay and Diener 2011; Sirgy 2011; Yetim 2011).…”
Section: Social Media and Community Well-beingmentioning
confidence: 99%